Assessment of the Effect of Pain on Daily Functioning of Patients with the Diagnosed Back Pain Syndrome - Regina Lorencowicz; Józef Jasik; Marlena Kołodyńska; Krzysztof Turowski (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. The back pain syndrome is one of the most common health problem of the contemporary society. Acute pain syndromes of the lower section of the spine affect 28 people per 1000 inhabitants. The disease more often affects men aged 25–64. In the population of one hundred thousand inhabitants 107 men and 64 women suffer from acute pain syndrome of the cervical spine. Most often the pain occurs between 50 and 54 years of age. Also, back pain syndromes constitute a serious economic problem for the contemporary society as they are statistically the most frequent in the case of men and the second in the case of women reason for absence from work, and in 20% of cases they indicate the necessity of granting disability pension due to permanent inability to work. Aim. Assessment of pain intensity effect on daily functioning of patients diagnosed with the back pain syndrome. Material and Methods. The research included 187 patients diagnosed with back pain syndrome aged from 20 to 83 years and it was carried out in April and May 2013. The diagnostic survey method and statistical analysis were applied. Results. The most difficult issue for the respondents in their daily functioning was to accept permanent pain stimuli (100%), permanent stiffness in the back or neck, (96.33%), copying with the pain when the performance of everyday duties required prolonged sitting or standing (99.47%) as well as the performance of daily household activities (100%). Back pain to greater or lesser extent resulted in the loss of control over major spheres of everyday life in the respondents, on average from 3.34 to 6.37 on the scale from 1 to 10 points. All respondents admitted having problems with remaining in the sitting position for a long time. The average loss of fitness in the group of respondents ranged 39.30±18.09 points (Me=37; range from 7 to 88 points). Based on the average value ± 1 SD it was stated that 16.58% (n=31) of respondents had light malfunction, whereas 65.78% (n=123) had moderate and 17.64% (n=33) serious. Conclusions. 1. Chronic back pain has a devastating impact on the daily functioning of patients with diagnosed spinal pain syndrome 2. The most difficult issue for the respondents in their daily functioning was to accept permanent pain stimuli 3. The average strength of the negative impact of the back pain on daily functioning ranged from 6.25 to 6.49 in the scale from 1 to 10 points. 4. All respondents admitted that back pain to greater or lesser extent resulted in a loss of control over major spheres of everyday life. 5. Just over a quarter of respondents (25.13%) did not have major problems, resulting from the pain, with the performance of daily duties at work. 6. For more than three quarters of the respondents (77.01%) pain while sitting in the chair for a few hours was a significant problem in everyday functioning. 7. The statistical analysis carried out, showed a significant correlation between the intensity of the back pain and lowering of physical fitness. (JNNN 2014;3(4):157–168)